2023
DOI: 10.1186/s12890-023-02563-9
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of postoperative rehabilitation interventions that include breathing exercises to prevent pulmonary atelectasis in lung cancer resection patients: a systematic review and meta-analysis

Abstract: Background The main aim of this systematic review was to determine the effectiveness of postoperative rehabilitation interventions that include breathing exercises as a component to prevent atelectasis in lung cancer resection patients. Methods In this review, we systematically and comprehensively searched the Cochrane Library, PubMed, EMBASE, and Web of Science in English and CNKI and Wanfang in Chinese from 2012 to 2022. The review included any r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Many systematic reviews and meta-analyses have shown that exercise interventions can significantly improve cardiopulmonary function and reduce the risk of respiratory diseases such as upper respiratory tract infections and pneumonia [ 33 ]. However, these recent meta-analyses presented somewhat negative results when assessing the effects of exercise on the psychological domains of pulmonary function and QOL in NSCLC patients after surgery [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many systematic reviews and meta-analyses have shown that exercise interventions can significantly improve cardiopulmonary function and reduce the risk of respiratory diseases such as upper respiratory tract infections and pneumonia [ 33 ]. However, these recent meta-analyses presented somewhat negative results when assessing the effects of exercise on the psychological domains of pulmonary function and QOL in NSCLC patients after surgery [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…At present, the clinical treatments of lung cancer include various methods such as surgical resection, chemotherapy, radiotherapy and molecular targeted therapy. [2] The treatment of lung cancer mainly depends on the patient condition and individual differences. [3] Therefore, the prevention and early detection of lung cancer is very important, which will help to improve the treatment effects and the survival rate of patients.…”
Section: Introductionmentioning
confidence: 99%